Kesadaran Halal Masyarakat terhadap Produk UMKM Makanan di Kota Bengkulu - Tri Wahyuni; Miti Yarmunida; Debby Arisandi (Universitas Batanghari Jambi, 2022)
Currently, MSME products continue to increase and are not optimistic in the food sector. MSME food products are not in the form of packaging but also there are only MSME business actors who provide food directly on the spot and the food ingredients come from meat. According to LPPOM MUI data, there are 318 MSME products recorded in Bengkulu Province. 162 is located in Bengkulu City. Along with the development of the halal lifestyle, people are more selective in choosing food by paying attention to the availability of halal labels in places to eat because not all MSME products are halal certified. For this reason, public awareness of halal is needed before consuming food, especially meat-based, this is related to animal slaughter. This study aims to find out whether the millennial generation understands what is meant by halal awareness and how the millennial generation's halal awareness of MSME Food products in Bengkulu City. The type of research used is descriptive qualitative with purposive sampling as the sample collection. The results of the study show that the millennial generation is aware of and understands the halal awareness of a religious obligation in carrying it out. The behavior or actions of the millennial generation are in line with the knowledge they have and their application in everyday life. Such as halal awareness to consume halal food and toys. Before consuming the millennial generation, first pay attention to the production process, packaging, raw materials or composition, cleanliness and safety and look for information on the availability of halal labels on the MSME products.